Efficient recovery and DNA extraction for algae-associated microbial communities - Chevokina, Elizaveta; Sibiryakina, Daria; Sobolev, Andrey; Slonova, Darya; Demkina, Alina; Yurikova, Daria; Galivondzhyan, Alina; Konovalova, Olga; Sutormin, Dmitry; Isaev, Artem (Frontiers in Plant Science, 2026)
The extraction of high-quality microbial DNA from environmental samples is critical for many downstream applications, including short- and long-read metagenomic sequencing. However, environmental DNA is prone to low recovery, degradation, and contamination by enzymatic inhibitors, with the extent of these issues largely dependent on the DNA purification method. The embedding of bacterial cells in a mucoid matrix within biofilms further complicates the process, making the study of algal symbionts particularly challenging. This study benchmarked five methods to recover microbial cells from biofilms associated with three major groups of marine macroalgae, namely: red (Palmaria stenogona), brown (Saccharina japonica), and green (Ulva lactuca). This was followed by a systematic evaluation of six widely used commercial DNA purification kits for their ability to extract high-quality DNA suitable for 16S rRNA gene and shotgun sequencing. A universal trade-off was observed between the quantity and quality of the extracted DNA. While whole-sample homogenization and manual collection of biofilms resulted in high levels of chloroplast contamination, washing microbial cells with a buffer led to low DNA recovery; however, the use of a detergent improved DNA yields. A comparison of the DNA extraction kits revealed that their efficiency varied significantly among algal species, with the GeneJET Genomic DNA Purification Kit (Thermo Scientific) identified as the most versatile. The present findings provide a comparative benchmark of methods to recover algae-associated microbial communities and extract their DNA, offering guidance in selecting procedures suited for metagenomic sequencing.